Transient stability indices from a hybrid approach - Padilha, A. [UNESP]; Denis, E. F. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This paper deals with hybrid method for transient stability analysis combining time domain simulation and a direct method. Nowadays, the step-by-step simulation is the best available tool for allowing the uses of detailed models and for providing reliable results. The main limitation of this approach involves the large time of computational simulations and the absence of stability margin. On the other hand, direct methods, that demand less CPU time, did not show ample reliability and applicability yet. The best way seems to be using hybrid solutions, in which a direct method is incorporated in a time domain simulation tool. This work has studied a direct method using the transient potential and kinetic energy of the critical machine only. In this paper the critical machine is identified by a fast and efficient method, and the proposal is new for using to get stability margins from hybrid approaches. Results from systems, like 16-machine, show stability indices to dynamic security assessment. © 2001 IEEE.
Keywords: Direct method; Dynamic security assessment; Terffis-transient stability; Trapezoidal rule; Computational simulation; CPU time; Critical machine; Detailed models; Hybrid approach; Hybrid method; Hybrid solution; Stability indices; Stability margins; Step-by-step; Time domain simulation tools; Time-domain simulations; Transient stability analysis; Transient stability indices; Trapezoidal rules; Computer simulation; Time domain analysis